The Impact of Digital Transformation on Company Net Profit - A. S. Melnikov; E. G. Kalabina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides findings of the econometric research, whose goal is to find links between the level of digital transformation at the enterprise and its finance results. The authors estimated the impact of digital transformation level on the company net profit. The research findings demonstrated the inverse relationship between the digital transformation level and the company net profit. This impact is higher for bigger companies, whose assets exceed 90 bn rubles in comparison with small companies. It can be explained by the fact that in companies, selected for the research, the process of digital technology and tool introduction is still going on or has just been finished, therefore their recoupment cannot start at once but a little later, as the introduction period is rather expensive. The research shows that we should not forget about the adverse aspect of digital transformation, i.e. prolonged periods of recoupment and the importance of choosing the correct digital tool for your industry. The present research can supplement the topic of restriction and risks of digital transformation for the company. The article could be useful for executives, finance analysts and investors, who make decisions about investment, as the research shows that company should thoroughly analyze its needs and opportunities before investing into digital technologies. It is important to develop a clear strategy and assess risks connected with new technology introduction.